2018
DOI: 10.1039/c8sm00126j
|View full text |Cite
|
Sign up to set email alerts
|

Flocking transitions in confluent tissues

Abstract: Collective cell migration in dense tissues underlies important biological processes, such as embryonic development, wound healing and cancer invasion. While many aspects of single cell movements are now well established, the mechanisms leading to displacements of cohesive cell groups are still poorly understood. To elucidate the emergence of collective migration in mechanosensitive cells, we examine a self-propelled Voronoi (SPV) model of confluent tissues with an orientational feedback that aligns a cell's po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
165
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 151 publications
(180 citation statements)
references
References 57 publications
11
165
0
Order By: Relevance
“…Another important question is whether a coupling between cell shape and cell motility could give rise to our observations, instead of tissue drag. Previous simulations using a similar model showed that cells tend to elongate slightly in the direction perpendicular to the direction of cell motility [53]. This effect is not dominant here, as the cell shape changes are not the same anteriorly (where cells are elongated parallel to the direction of motion) and posteriorly (where cells are elongated perpendicular to the direction of motion).…”
Section: Discussionmentioning
confidence: 60%
“…Another important question is whether a coupling between cell shape and cell motility could give rise to our observations, instead of tissue drag. Previous simulations using a similar model showed that cells tend to elongate slightly in the direction perpendicular to the direction of cell motility [53]. This effect is not dominant here, as the cell shape changes are not the same anteriorly (where cells are elongated parallel to the direction of motion) and posteriorly (where cells are elongated perpendicular to the direction of motion).…”
Section: Discussionmentioning
confidence: 60%
“…Other studies have focused on the onset of collective motion, showing that cell-autonomous polarity-velocity alignment ( Fig. 5c and Section 2.4.1) gives rise to emergent cell-cell alignment, which leads to coherent rotations [114] and flocking [68,108,115]. Altogether, SPV models predict four distinct phases: solid, liquid, solid flock, and liquid flock (Fig.…”
Section: Collective Phenomenamentioning
confidence: 90%
“…b, Cells are parametrized by an area Ai and a perimeter Pi, and experience a self-propulsion force Ta pi (orange) and an interaction force F int i = − ∇ r i F (dashed black), which give the resultant force (black). Adapted from[108] with permission from The Royal Society of Chemistry. c, Polarity-velocity alignment with a time-scale τ .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…RAB5A further promotes millimetres-scale, ballistic locomotion of multicellular streams by augmenting the extension of oriented and persistent RAC1-driven, protrusions 31 . These effects combine to endow monolayers with a flocking fluid mode of motion, which is explained in numerical simulations in terms of large scale coordinated migration and local unjamming, driven by an increased capability of each individual cell to align its velocity to the one of the surrounding group 31-33 . Molecularly, impairing endocytosis, macropinocytosis or increasing fluid efflux abrogated RAB5A-induced collective motility, suggesting that perturbations of trafficking processes impacting on different signalling and biomechanical pathways are necessary for the JUT.…”
Section: Introductionmentioning
confidence: 99%